Biochemical, Physiological and Anatomical Mechanisms of Adaptation of Callistemon citrinus and Viburnum lucidum to NaCl and CaCl2 Salinization - Cirillo, Chiara; De Micco, Veronica; Arena, Carmen; Carillo, Petronia; Pannico, Antonio; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2019)
Callistemon citrinus and Viburnum lucidum are appreciated and widespread ornamental shrubs for their abundant flowering and/or brilliant foliage. The intrinsic tolerance to drought/salinity supports their use in urban areas and in xeriscaping. Despite adaptive responses of these ornamental species to sodium chloride (NaCl) have been extensively explored, little is known on the effects of other salt solution, yet iso-osmotic, on their growth, mineral composition and metabolism. The present research was aimed to assess responses at the biochemical, physiological and anatomical levels to iso-osmotic salt solutions of NaCl and CaCl2 to discriminate the effects of osmotic stress and ion toxicity. The two ornamental species developed different salt-tolerance mechanisms depending on the salinity sources. The growth parameters and biomass production decreased under salinization in both ornamental species, independently of the type of salt, with a detrimental effect of CaCl2 on C. citrinus. The adaptive mechanisms adopted by the two ornamental species to counteract the NaCl salinity were similar, and the decline in growth was mostly related to stomatal limitations of net CO2 assimilation rate, together with the reduction in leaf chlorophyll content (SPAD index). The stronger reduction of C. citrinus growth compared to V. lucidum, was due to an exacerbated reduction in net photosynthetic rate, driven by both stomatal and non stomatal limitations. In similar conditions, V. lucidum exhibited other additional adaptive response, such as modification in leaf functional anatomical traits, mostly related to the reduction in the stomata size allowing plants a better control of stomata opening than in C. citrinus. However, C. citrinus plants displayed an increased ability to retain higher Cl- levels in leaves than in roots under CaCl2 salinity compared to V. lucidum, thus, indicating a further attempt to counteract chloride toxicity through an increased vacuolar compartmentalization and to take advantages of them as chip osmotica.